Tink, north of Never Land - Thorpe, Kiki.; Clarke, Judith; Brown, Adrienne; Pickens, Charles (New York : Random House, 2007)
After realizing that it was her angry outburst that drove away her friend Terence, Tinker Bell sets out on a dangerous quest to bring him a spectacular gift.
"A Stepping Stone book."
Keywords: Friendship; Fairies; Adventure and adventurers